Resistance Mechanism of Plants against Cadmium: A Review - John, Riffat; Gadgil, Kasturi; Sharma, Satyawati (Asian Journal of Chemistry, 2016)
Cadmium in soils is known to originate from geogenic (natural) and anthropogenic (industrial) sources. Cadmium in soils is known to be more mobile and readily absorbed and incorporated into plant tissues compared with lead and mercury. Due to inherent genetic and physiological characteristics plants have long been known to accumulate cadmium from soils. Some plants known as hyperaccumulators are able to tolerate high levels of elements in the root and shoot cells. The ability to both tolerate elevated levels of heavy metals and to accumulate them to unusually high concentrations is the result of various biological mechanisms which plants have developed during evolution. Phytoremediation is the use of specially selected and engineered metal accumulating plants for environmental clean-up.